An Ultrastable and Dense Single‐Molecule Click Platform for Sensing Protein–Deoxyribonucleic Acid Interactions. Issue 5 (23rd February 2021) - Visser, Emiel W. A.; Miladinovic, Jovana; Milstein, Joshua N.
Abstract: An ultrastable, highly dense single‐molecule assay ideal for observing protein–DNA interactions is demonstrated. Stable click tethered particle motion leverages next generation click‐chemistry to achieve an ultrahigh density of surface tethered reporter particles, and has low non‐specific interactions, is stable at elevated temperatures to at least 45 °C, and is compatible with Mg 2+, an important ionic component of many regulatory protein–DNA interactions. Prepared samples remain stable, with little degradation, for >6 months in physiological buffers. These improvements enable the authors to study previously inaccessible sequence and temperature‐dependent effects on DNA binding by the bacterial protein, histone‐like nucleoid‐structuring protein, a global transcriptional regulator found in Escherichia coli . This greatly improved assay can directly be translated to accelerate existing tethered particle‐based, single‐molecule biosensing applications. Abstract : An ultrastable, highly dense single‐molecule assay ideal for observing protein–DNA interactions is demonstrated. This system enables one to study previously inaccessible sequence‐ and temperature‐dependent effects on DNA binding by the bacterial protein H‐NS, a global transcriptional regulator found in Escherichia coli . This greatly improved assay can directly be translated to accelerate existing tethered particle‐based, single‐molecule biosensing applications.